(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
We studied cultured peripheral blood (PB) and/or bone marrow (BM) cells of 48 patients with chronic myeloid leukemia from Hematological Center of Armenia. There were 29 women (age 10–82 years) and 19 men (age 20–82 years). On the basis of clinical and hematological data all patients are divided into 2 groups; in the 1-st group 41 patients are involved (in chronic phase), in the 2-nd group – 7 patients (in blast crisis phase). 38 patients (93%) of 41 from the 1-st group have typical chromosome translocation t(9;22) (q34, q11) (Philadelphia chromosome) in bone marrow and/or peripheral blood cells. There was no correlation between obtained results on Ph+ with age and sex in the investigated group. In the 2-nd group together with Ph-chromosome in 7 (17%) patients is indicated extra Ph-chromosome, i(17q), trisomy 8, trisomy 19, marker.